2020
DOI: 10.15390/eb.2020.8823
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Writing Based on Flipped Classroom Model on Metacognitive Writing Awareness and Writing Achievements of Middle-School Students

Abstract: Bu makale Hasan Basri Kansızoğlu'nun Özlem Bayrak Cömert danışmanlığında yürüttüğü "Ters yüz edilmiş sınıf modeline dayalı yazma öğretiminin öğrencilerin üstbilişsel farkındalık düzeylerine, yazma başarılarına ve kaygılarına etkisi" başlıklı doktora tezinden üretilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…After the application, there was a significant difference between the experimental and control groups according to the SEMAT post-test and permanence tests in the HSELS (Tables 3 and 4). This finding is in line with numerous studies (Alamri, 2019;Ali et al 2021;Bergmann & Sams, 2012;Çakır & Yaman, 2018;Davies et al 2013;Ghanaat & Habibzadeh, 2021;Kansızoğlu & Cömert, 2021;MacKinnon, 2015;Ok, 2019;Pierce & Fox, 2012;Yıldız et al 2016;Zhao et al 2021).…”
Section: Discussionsupporting
confidence: 86%
“…After the application, there was a significant difference between the experimental and control groups according to the SEMAT post-test and permanence tests in the HSELS (Tables 3 and 4). This finding is in line with numerous studies (Alamri, 2019;Ali et al 2021;Bergmann & Sams, 2012;Çakır & Yaman, 2018;Davies et al 2013;Ghanaat & Habibzadeh, 2021;Kansızoğlu & Cömert, 2021;MacKinnon, 2015;Ok, 2019;Pierce & Fox, 2012;Yıldız et al 2016;Zhao et al 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding metacognition in writing, several studies have demonstrated effective interventions. These interventions include the use of reflective writing journals to foster deeper self-reflection (Loughlin & Griffith, 2020;Ramadhanti et al, 2020), the integration of active learning and metacognitive feedback (Zhang & Li, 2021), web-based instructional strategies (Arroyo González et al, 2021), metacognitive support groups , cooperative-metacognitive instructional approach , mobile-assisted language learning tools (Kessler, 2021), metacognitive prompts to enhance awareness (Teng, 2021), and the flipped classroom model to invert traditional learning environments (Kansızoğlu & Bayrak Cömert, 2020).…”
Section: Research Papersmentioning
confidence: 99%
“…Contrary to such traditional practices, students should be guided to plan, analyze and participate in the writing process in a rich learning environment that motivates students and fosters their autonomy and involvement. Kansizoglu and Comert (2021) state that systematic review and meta-analysis studies include practical solutions to insufficient writing instruction; they include increasing students' knowledge of writing, providing sufficient time and feedback on writing; teaching students how to plan, draft and edit, creating supportive writing environments, adopting a processbased writing approach, and emphasizing metacognitive skills. Purpose, context, and audience are complexly related; students must know why they are writing and their intended audience (Pytash & O'byrne, 2014).…”
Section: A Writing Instructionmentioning
confidence: 99%